PENGARUH VISUAL MERCHANDISING DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING MELALUI POSITIVE EMOTION - Kusmayadi, Andri; Fitrian, Devi Arum (STIE Mahardhika, 2025)
Impulse buying contributes greatly to a company's revenue and profitability, making it one of the most important elements for a business. With the existence of impulse buying, retail stores in Indonesia offer various advantages in providing attractive services to consumers. One of the factors that can influence impulse buying is visual merchandising, store atmosphere, and positive emotion. This research uses a purposive sampling technique, where the sample method used is Non-Probability Sampling. The data analysis technique used in this research uses Partial Least Square. PLS testing uses two models, namely the outer model test and the inner model test. Outer model testing consists of validity tests including convergent validity and discriminant validity, while reliability tests include composite reliability and Cronbach's alpha. Inner model testing consists of goodness of fit and path coefficient. The results of this research are, Visual merchandising has a positive effect on positive emotion, store atmosphere has a positive effect on positive emotion, visual merchandising has a positive effect on impulse buying, store atmosphere has a positive effect on impulse buying, visual merchandising has no effect on impulse buying through positive emotion and store atmosphere has no effect on impulse buying through positive emotion. It is hoped that this research can contribute to the theoretical/scientific level of management and also increase sales at KKV stores in the DKI Jakarta area.